MANAGEMENT OF COMMUNITY LEARNING PROGRAM ON MERDEKA TEACHING PLATFORM IN AMBON - Husein, Vanda Festari; Kempa , Rudolf; Rumfot , Sumarni (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to analyze the planning, organization, implementation, supervision, evaluation of programs, and supporting and inhibiting factors of the Ahmad Dahlan SD Muhammadiyah 2 Ambon learning community and the Walang SD Inpres 25 Ambon learning community in PMM. The type of research used is phenomenological research with a qualitative approach. Data collection techniques include interviews, observations, and document studies. Data analysis techniques use interactive analysis. The research results indicate that (1) The planning of the Ahmad Dahlan SD Muhammadiyah 2 Ambon and SD Inpres 25 Ambon learning community programs has been carried out in accordance with the strategic plan; (2) The organization of the Ahmad Dahlan learning community program at SD Muhammadiyah 2 Ambon and SD Inpres 25 Ambon has been structured based on schedules, time allocation, supporting resources, and the division of tasks among each member of the learning community; (3) The implementation of the Ahmad Dahlan learning community program at SD Muhammadiyah 2 Ambon and SD Inpres 25 Ambon has been carried out in accordance with the methods, techniques, and guidance; (4) Supervision of the Ahmad Dahlan community learning program at SD Muhammadiyah 2 Ambon and SD Inpres 25 Ambon has been carried out directly; (5) Evaluation of the Ahmad Dahlan community learning program at SD Muhammadiyah 2 Ambon and the Walang community learning program at SD Inpres 25 Ambon has been carried out according to plan; (6) Supporting and inhibiting factors of the Ahmad Dahlan community learning program at SD Muhammadiyah 2 Ambon and SD Inpres 25 Ambon: all elements of the learning community are cooperative, solid, creative, and competent in planning, organizing, and carrying out their tasks. Inhibiting factors of the community learning program lie in internet access, the school environment, and the budget.